Avaliação da posição do incisivo central superior em relação às corticais ósseas e a indicação para a aplicação de torques ortodônticos: estudo em tomografias computadorizadas de feixe cônico - Faggioni, Marina Santos (2021)
There are different types of orthodontic bracket prescriptions. However, the correct indication of these is neglected by professionals indicating a single type of pre-adjusted bracket for all patients. Bone and dental morphology can influence treatment success and complications such as bone fenestrations can occur. The objective of this study was to analyze the risk of contact between the maxillary central incisor root (ICS) and the bone cortex, in different bracket prescriptions, taking into account the diagnostic variables of the amount of bone thickness and the initial inclination of the root of this through digital simulation of segmented CBCT models. From a collection of 100 CBCT exams, from adult individuals, the 1 .SN and 1.NA angles, the alveolar thickness and the initial position of the ICS in the alveolar process were evaluated. Subsequently, out of 20 exams, 3D segmentations of the maxilla and teeth were performed and a digital simulation was performed, inserting the final torque of the Straight Wire, Roth and MBT prescriptions for the ICS, evaluating the final position and the risk of contact. It was found that the prescription of lower risk is influenced by the initial position of the incisor within the maxillary bone, while there was no relationship with previous inclination. The orthodontic movement simulations showed that there are risks of contact between the roots and the alveolar bone cortical depending on the torque applied, while for each case a prescription showed better results, influenced by the initial position of the root.